Improving Customer Service Performance Using PPT and SECI: A Literature Review of Bluegreen Bank Case - Benedicta Anggit Sekartaji; Dedy Sushandoyo (Integrasi Sains Media, 2025)
Customer service is crucial in the banking industry, directly impacting customer satisfaction, trust, and overall business performance. However, many financial institutions face challenges in managing knowledge effectively, leading to inconsistent service quality, operational inefficiencies, and regulatory compliance risks. This study examines the role of Knowledge Management (KM) in enhancing customer service performance, with a specific focus on the People, Process, and Technology (PPT) framework and the SECI Model (Socialization, Externalization, Combination, and Internalization). Through a systematic literature review (SLR), this study synthesizes insights from academic research on KM implementation in banking customer service, identifying key benefits, challenges, and best practices. The findings reveal that effective KM adoption significantly improves service accuracy, reduces response times, and enhances customer engagement by ensuring service representatives have instant access to structured knowledge repositories. Furthermore, KM facilitates regulatory compliance and data security by providing automated updates on financial policies, fraud prevention measures, and data protection standards. However, barriers such as employee resistance, fragmented knowledge systems, and outdated IT infrastructure hinder the implementation of KM frameworks in banking institutions. To address these challenges, this study recommends integrating AI-driven KM platforms, standardizing knowledge-sharing practices across branches, and fostering a knowledge-sharing culture through training and incentives. Banks can leverage structured KM frameworks to enhance operational efficiency, build long-term customer loyalty, and strengthen their position in an increasingly digitalized financial landscape. Future research should explore the role of AI and emerging technologies in optimizing KM practices for customer service excellence.